Design and Implementation of Arduino-Based PID Control System for Water Level Regulation Using Ultrasonic Sensors - Efendi, Mas; Candra, Feri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
Water resource management is a critical aspect of various sectors, including agriculture, industry, and household applications, where maintaining optimal water levels is essential for efficiency, sustainability, and safety. Traditional water level control methods often rely on manual operations, leading to inefficiencies, resource wastage, and potential system failures. To address these challenges, this study presents the design and implementation of an automated water level control system using a Proportional-Integral-Derivative (PID) controller, an HC-SR04 ultrasonic sensor, and an Arduino Uno microcontroller. The system is designed to enhance accuracy and reliability in liquid level regulation, particularly in industrial and domestic settings. By systematically tuning the Proportional Gain (Kp), Integral Gain (Ki), and Derivative Gain (Kd), the optimal parameter values were determined as Kp = 20.0, Ki = 11.0, and Kd = 1.0. Experimental results demonstrated that the proposed system achieves stable water level regulation with rapid response times and minimal deviations. This research contributes to the advancement of automated liquid control technologies, offering a cost-effective and efficient solution for real-world water management applications.